Pesantren Curriculum Integration in Indonesia - imron muttaqin (Arfannur, 2023)
This study aims to explore pesantren curriculum integration in Indonesia; the rapid development of pesantren today. And all types and variations are interesting to study, especially the curriculum models used by pesantren. Methods: This research uses literature studies, data analysis is carried out by content analysis, and data sources are obtained from articles in scientific journals that have been published. Results: The results show that the model of integration of the Islamic boarding school curriculum in Indonesia varies and gradually, not using only one model but a combination of various forms according to the level of students. The basic level uses cellular, connected, and integrated models; at high levels, it uses immersed and networked models. Suggestion: Various models of integrating the pesantren curriculum in Indonesia are inseparable from the background and socioculture of pesantren and the surrounding community. Therefore, it is recommended that Islamic boarding schools that intend to develop a curriculum involve the community to know what the needs directly and pay attention to technological developments.